The Cognitive Atlas: Toward a Knowledge Foundation for Cognitive Neuroscience - Poldrack, Russell A.; Kittur, Aniket; Kalar, Donald; Miller, Eric; Seppa, Christian; Gil, Yolanda; Parker, D. S.; Sabb, Fred W.; Bilder, Robert M. (Frontiers in Neuroinformatics, 2011)
Cognitive neuroscience aims to map mental processes onto brain function, which begs the question of what ``mental processes'' exist and how they relate to the tasks that are used to manipulate and measure them. This topic has been addressed informally in prior work, but we propose that cumulative progress in cognitive neuroscience requires a more systematic approach to representing the mental entities that are being mapped to brain function and the tasks used to manipulate and measure mental processes. We describe a new open collaborative project that aims to provide a knowledge base for cognitive neuroscience, called the Cognitive Atlas (accessible online at http://www.cognitiveatlas.org), and outline how this project has the potential to drive novel discoveries about both mind and brain.